Sammlung 1968 Karl Ströher. - Haus der Kunst, München (München : Galerie-Verein, 1968)
Andre, Carl ; Artschwager, Richard ; Bacon, Francis ; Beuys, Joseph ; Chamberlain, John ; Dine, Jim ; Dubuffet, Jean ; Ernst, Max ; Flavin, Dan ; Indiana, Robert ; Johns, Jasper ; Klein, Yves ; Kurillof ; Lichtenstein, Roy ; Manzoni, Piero ; Louis, Morris ; Mathieu, Georges ; Enchauren Matta, Roberto ; etc.
Sammlung 1968 Karl Ströher, Galerie-Verein, München, Neue Pinakothek, Haus der Kunst, Westflügel, 14. Juni - 9. August 1968
boek